AMOBES (Active Mobility Very Early After Stroke): A Randomized Controlled Trial. Issue 2 (February 2017) - Yelnik, Alain P.; Quintaine, Victorine; Andriantsifanetra, Cedric; Wannepain, Marie; Reiner, Peggy; Marnef, Hélène; Evrard, Mathilde; Meseguer, Elena; Devailly, Jean Pascal; Lozano, Monica; Lamy, Catherine; Colle, Florence; et al.
Abstract : Background and Purpose—: Intensive physical therapy (PT) facilitates motor recovery when provided during a subacute stage after stroke. The efficiency of very early intensive PT has been less investigated. We aimed to investigate whether intensive PT conducted within the first 2 weeks could aid recovery of motor control. Methods—: This multicentre randomized controlled trial compared soft PT (20-min/d apart from respiratory needs) and intensive PT (idem+45 minutes of intensive exercises/day) initiated within the first 72 hours after a first hemispheric stroke. The primary outcome was change in motor control between day (D) 90 and D0 assessed by the Fugl–Meyer score. Main secondary outcomes were number of days to walking 10 m unassisted, balance, autonomy, quality of life, and unexpected medical events. All analyses were by intent to treat. Results—: We could analyze data for 103 of the 104 included patients (51 control and 52 experimental group; 64 males; median age overall 67 [interquartile range 59–77], 67 right hemispheric lesions, 80 ischemic lesions, National Institutes of Health Stroke Scale score ≥8 for 82%). Fugl–Meyer score increased over time ( P <0.0001), with no significant effect of treatment ( P =0.29) or interaction between treatment and time ( P =0.40). The median change in score between D90 and D0 was 27.5 (12–40) and 22.0 (12–56) for control and experimental groups ( P =0.69). Similar results were found for the secondary criteria. Conclusions—: Very early after stroke, intensive exercises may not be efficient in improving motor control. This conclusion may apply to mainly severe stroke. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01520636. Abstract : Supplemental Digital Content is available in the text.